2010
DOI: 10.1002/arch.20374
|View full text |Cite
|
Sign up to set email alerts
|

Screening of T7 phage displayed Bactrocera dorsalis (Hendel) antenna cDNA library against chemosensory protein

Abstract: Recent studies have shown that chemosensory proteins (CSPs) were involved in diverse life activities such as insect feeding, development, mating, immune regulation, as well as other important circadian rhythms, etc. To screen the proteins involved in the BdorCSP-related physiological activity, a cDNA library of the Bactrocera dorsalis (Hendel) antenna expressed on the surface of T7 phage was screened against BdorCSP. After four rounds of screening, ELISA-positive samples of selected phages were sequenced and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Later studies identified other members of this family in sensory appendages such as antennae, labial palps and legs in a variety of insects [10] [11] . Several members of this class of protein have been described in insects of different orders, including Lepidoptera [11] [19] , Orthoptera [10] , [20] [22] , Hymenoptera [7] , [23] [26] , Diptera [27] , Blattoidea [28] – [29] , Phasmatodea [30] [32] , Hemiptera [33] , etc. The function of CSPs as carrier proteins was strengthened by studies on the higher order structure of a CSP from Bombyx mori , which revealed a globular configuration of six alpha helices surrounding a hydrophobic binding pocket [34] .…”
Section: Introductionmentioning
confidence: 99%
“…Later studies identified other members of this family in sensory appendages such as antennae, labial palps and legs in a variety of insects [10] [11] . Several members of this class of protein have been described in insects of different orders, including Lepidoptera [11] [19] , Orthoptera [10] , [20] [22] , Hymenoptera [7] , [23] [26] , Diptera [27] , Blattoidea [28] – [29] , Phasmatodea [30] [32] , Hemiptera [33] , etc. The function of CSPs as carrier proteins was strengthened by studies on the higher order structure of a CSP from Bombyx mori , which revealed a globular configuration of six alpha helices surrounding a hydrophobic binding pocket [34] .…”
Section: Introductionmentioning
confidence: 99%